New Educator Roles for Health Systems Science: Implications of New Physician Competencies for U.S. Medical School Faculty. (April 2019) - Gonzalo, Jed D.; Chang, Anna; Wolpaw, Daniel R.
Abstract : To address gaps in U.S. health care outcomes, medical education is evolving to incorporate new competencies, as well as to align with care delivery transformation and prepare systems-ready providers. These new health systems science (HSS) competencies—including value-based care, quality improvement, social determinants of health, population health, informatics, and systems thinking—require formal education and role modeling in both classroom and clinical settings. This is challenging because few faculty had formal training in how to practice or teach these concepts. Thus, these new competencies require both expanding current educators' skills and a new cohort of educators, especially interprofessional clinicians. Additionally, because interprofessional teams are the foundation of many clinical learning environments, medical schools are developing innovative experiential activities that include interprofessional clinicians as teachers. This combination of a relative "expertise vacuum" within the current cohort of medical educators and expanding need for workplace learning opportunities requires a reimagining of medical school teachers. Based on experiences implementing HSS curricula at two U.S. medical schools (Penn State College of Medicine and University of California, San Francisco, School of Medicine, starting in 2013), this Perspective explores the need for new educator competencies and the implications for medical education, including the need to identify and integrate "new" educators into the education mission, develop faculty educators' knowledge and skills in HSS, and acknowledge and reward new and emerging educators. These efforts have the potential to better align the clinical and education missions of academic health centers and cultivate the next generation of physician leaders.